Assessing patients' and GPs' ability to recognise overweight and obesity. (3rd July 2016) - Wong, Carmen; Harrison, Christopher; Bayram, Clare; Miller, Graeme
Abstract: Objective : To assess the ability of GPs and patients to recognise overweight and obesity, determine factors associated with accurate weight perception, and identify methods used by patients and GPs to manage patient overweight and obesity. Methods : Data were collected in a substudy of the BEACH research program (a continuous, randomised, national cross‐sectional survey of general practice activity in Australia). Results : Of 1, 599 sampled adult patients, 31.5% were overweight, 23.7% obese and 4.7% morbidly obese. One in four (26.8%) overweight/obese patients (BMI ≥25.0) did not consider themselves overweight. There was an association between patient age and sex and accurate weight perception. Overweight/obese females and those aged 45–64 years were most likely to recognise their overweight. GPs correctly identified 60.8% of overweight patients, but underestimated 35.7% as normal weight. They also identified 60.0% of obese patients, but incorrectly categorised 37.0% as overweight and 3.0% normal weight. There was no association between GP age and sex and accurate weight perception. Conclusions : Patients' and GPs' perception of weight can often be inaccurate, with many not recognising overweight and obesity. Improvement in recognition of overweight and obesity may increase management and encourage early intervention to prevent disease associated with these weight problems.